2009
DOI: 10.1590/s0100-736x2009000700001
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factors of avian pathogenic Escherichia coli (APEC)

Abstract: ABSTRACT.-Nakazato G., Campos T.A., Stehling E. Avian pathogenic Escherichia coli (APEC) strains cause a great diversity of diseases in birds and are responsible for great economic losses in the avian industry. To date, several studies have been carried out to better understand the APEC pathogenesis for a possible development of tools which could prevent the economics losses caused by these strains. This review discusses the virulence factors described do date to be expressed by these strains and the advances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 97 publications
(90 reference statements)
1
42
0
11
Order By: Relevance
“…It means that the absence of a virulence gene does not lead to the absence of associated phenotype. It implies that different strains of APEC could apply alternative approaches to infect the host (Nakazato et al 2009). It is recommended that overlay effects and alternatives of these factors and associated genes be investigated regarding to region (Dias da Silveira et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It means that the absence of a virulence gene does not lead to the absence of associated phenotype. It implies that different strains of APEC could apply alternative approaches to infect the host (Nakazato et al 2009). It is recommended that overlay effects and alternatives of these factors and associated genes be investigated regarding to region (Dias da Silveira et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The potentially pathogenic E. coli strains can be screened by different tests, like phenotypic assays as Congo red binding (Styles & Flammer 1991), serotyping (Schremmer et al 1999), and genotypic assays (Pakpinyo et al 2002, Knöbl et al 2008, Nakazato et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Virulence factors associated with APEC isolated from chickens, turkeys and ostriches include colonization factors (ϐimbrial and aϐimbrial adhesins), invasive factors, serum resistance mechanisms, iron acquisition systems, antiphagocytic activity and production of toxins (Knöbl et al 2001, Monroy et al 2005, Nakazato et al 2009). Well--recognized virulence properties include Type 1 (F1) and P ϐimbriae, IbeA proteases and aerobactin production, Iss for serum survival, K and O antigens for anti-phagocyitc activity, and a temperature-sensitive haemagglutinin of unknown function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations have reported serum resistance VGs are widespread among APEC in comparison with AFEC and have suggested that these VGs contribute to APEC pathogenicity (Delicato et al, 2003;Dozois et al, 1992;Dziva and Stevens, 2008;Lynne et al, 2007;Mellata et al, 2003;Mellata et al, 2012;Nolan et al, 2002;Ozawa et al, 2008;Rocha et al, 2008;Rodriguez-Siek et al, 2005a;Skyberg et al, 2008;Tivendale et al, 2004;Wooley et al, 1992;Yaguchi et al, 2007;Yang et al, 2004;Zhao et al, 2005). Several VGs have been linked with serum resistance mechanisms and the association of each of the serum resistance VGs with APEC pathogenicity mechanisms have also been independently studied (Nakazato et al, 2009;Rocha et al, 2008). However, limited information is known in regards to the presence of different serum resistance VG combinations and their contribution to APEC pathogenicity (Jeffrey et al, 2002;Nolan et al, 2002;Nolan et al, 2003;Sello, 2012).…”
Section: Serum Resistancementioning
confidence: 99%